The Development and Psychometric Properties of Geriatric Existential Anxiety Scale - Hemin Saadati; Bahman Bahmani (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective: The elderly is now struggling with various existential dimensions because they went through difficult life experiences. Due to the absence of any special tool to evaluate the dimensions of existential anxiety in the elderly, this study is aimed to develop a tool to study the dimensions of existential anxiety in the elderly and analyze its factors.Method: This research is a descriptive study, and its statistical population consists of the elderly (men and women) who are 60 years old and above and living in Tehran. In this study, 350 elderly people (male and female) were selected from this population using the multi-stage cluster sampling method. The research tools included the Existence Anxiety Scale, Beck Anxiety Inventory, Beck Depression Inventory, Psychological Flexibility Questionnaire, and Anxiety about Aging scale. The methods of exploratory factor analysis and confirmatory factor analysis, criterion validity, and convergent validity and divergent validity were used to evaluate the validity of the scale. And its reliability was assessed by two methods of internal consistency (Cronbach’s alpha) and stability of results (retest) with an interval of two weeks.Results: The exploratory factor analysis with the principal component analysis method and Varimax rotation has led to the extraction of 4 factors. The indicators of confirmatory factor analysis confirmed the existence of the four factors. It has indicated the acceptable correlations between the scale of Anxiety about Aging and its components with other valid parallel tools of criterion validity, convergent validity, and divergent validity of the scale. The reliability coefficients were obtained by the Cronbach’s alpha method and the retest reliability gained at a satisfactory level. Conclusion: The Anxiety about Aging scale is a valid and reliable self-assessment tool to evaluate the level of existential anxiety and its dimensions in the elderly, and it can be used for future activities and researches.